The role of GαO‐mediated signaling in the rostral ventrolateral medulla oblongata in cardiovascular reflexes and control of cardiac ventricular excitability. Issue 15 (15th August 2016) - Ang, Richard; Abramowitz, Joel; Birnbaumer, Lutz; Gourine, Alexander V.; Tinker, Andrew
Abstract: The heart is controlled by the sympathetic and parasympathetic limbs of the autonomic nervous system with inhibitory signaling mechanisms recruited in both limbs. The aim of this study was to determine the role of inhibitory heterotrimeric G proteins in the central nervous mechanisms underlying autonomic control of the heart and its potential role in arrhythmogenesis. Mice with conditional deletion of the inhibitory heterotrimeric G protein G α O in the presympathetic area of the rostral ventral lateral medulla (RVLM) were generated to determine the role of GαO‐mediated signalling in autonomic control and electrophysiological properties of the heart. G α O deletion within the RVLM was not associated with changes in heart rate (HR) or the arterial blood pressure at rest (home cage, normal behavior). However, exposure to stressful conditions (novel environment, hypoxia, or hypercapnia) in these mice was associated with abnormal HR responses and an increased baroreflex gain when assessed under urethane anesthesia. This was associated with shortening of the ventricular effective refractory period. This phenotype was reversed by systemic beta‐adrenoceptor blockade, suggesting that G α O depletion in the RVLM increases central sympathetic drive. The data obtained support the hypothesis that G α O ‐mediated signaling within the presympathetic circuits of the RVLM contributes to the autonomic control of the heart. G α O deficiency in the RVLM has a significant impact on cardiovascular responses to stress, cardiovascular reflexes and electrical properties of the heart. Abstract : This study aimed to determine the role of inhibitory heterotrimeric G proteins in the central mechanisms underlying autonomic control of the heart and its potential role in arrhythmogenesis. Mice with G α O deletion in the pre‐sympathetic area of the rostral ventral lateral medulla (RVLM) exposed to stressful conditions (novel environment, hypoxia or hypercapnia) had exaggerated heart rate responses and an increased baroreflex gain. This was associated with shortening of the ventricular effective refractory period. G α O deficiency in the RVLM is associated with exaggerated cardiovascular responses to stress, altered cardiovascular reflexes and electrical properties of the heart.